Pattern Of Scoliosis In Indian Population - Reddy P.D; Dave P.K; Kotwal P.P (Wolters Kluwer Medknow Publications, 1987)
This paper analyses the scoliotic curves in 100 Indian patients who attended Scoliosis Clinic at the All India Institute of Medical Sciences, New Delhi, between January 1982 and December 1983. We found that Idiopathic scoliosis was the commonest and both sexes were equally affected. Majority of the curves were to the right side. The incidence of Infantile Idiopathic scoliosis was very insignificant. Congenital scoliosis was second commonest Incidence of paralytic scoliosis was much less in spite of poliomyelitis being common in India. We have presented a detailed analysis of various curved and also the role of muscle imbalance in the production and progression of scoliosis.